2017
DOI: 10.1007/s10531-016-1286-4
|View full text |Cite
|
Sign up to set email alerts
|

Local and landscape scale determinants of macroinvertebrate assemblages and their conservation value in ponds across an urban land-use gradient

Abstract: Urbanisation represents a growing threat to natural communities across the globe. Small aquatic habitats such as ponds are especially vulnerable and are often poorly protected by legislation. Many ponds are threatened by development and pollution from the surrounding landscape, yet their biodiversity and conservation value remain poorly described. Here we report the results of a survey of 30 ponds along an urban land-use gradient in the West Midlands, UK. We outline the environmental conditions of these urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 97 publications
9
42
1
3
Order By: Relevance
“…In natural ponds, the presence of dense beds of macrophytes (submerged, emergent, and fringing) provides important habitat for numerous species. Consequently, many have pushed for artificial ponds to be similarly vegetated (Abellan et al, ; Goertzen & Suhling, ; Noble & Hassall, ; Rooney & Bayley, ; Thornhill, Batty, Death, Friberg, & Ledger, ). However, even when macrophytes are present in artificial ponds they are often periodically removed by managers, particularly when they hinder the primary function of the pond.…”
Section: How To Improve Artificial Ponds For Promoting Biodiversitymentioning
confidence: 99%
“…In natural ponds, the presence of dense beds of macrophytes (submerged, emergent, and fringing) provides important habitat for numerous species. Consequently, many have pushed for artificial ponds to be similarly vegetated (Abellan et al, ; Goertzen & Suhling, ; Noble & Hassall, ; Rooney & Bayley, ; Thornhill, Batty, Death, Friberg, & Ledger, ). However, even when macrophytes are present in artificial ponds they are often periodically removed by managers, particularly when they hinder the primary function of the pond.…”
Section: How To Improve Artificial Ponds For Promoting Biodiversitymentioning
confidence: 99%
“…The high contribution of species turnover to beta-diversity within urban ponds in individual urban settlements most likely reflects the wide variety of anthropogenic uses of urban ponds (e.g., stormwater retention, aesthetics, sediment collection and biodiversity) and the different management practices which they are subject to. The small catchment areas of ponds (Williams et al 2003) and the different management practices promotes a wide range of successional stages and environmental conditions across urban areas for macroinvertebrate taxa to utilise (Hill et al 2015;Thornhill et al 2017a). Previous studies have demonstrated that variation in local environmental conditions are often the principle regulator of species turnover in pond systems as macroinvertebrate taxa are essentially filtered by environmental gradients (Cottenie 2005;Hill et al 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have highlighted the potential conservation value of ponds [2,3], which is closely linked to macrophyte diversity [19,57]. The present study was limited to the presence of emergent, submerged and floating vegetation based on visual observations, allowing for an underestimation in larger, deeper water bodies, in particular regarding the presence of submerged vegetation.…”
Section: Pond Vs Lakementioning
confidence: 97%
“…By contrast, the typically reduced catchment area of ponds allows for the possibility that these ecosystems can avoid some of the impacts that plague water bodies with large catchments [18,19]. Previously cited effects of urbanization upon the water quality of still waters are nutrient concentration increases [19,20], greater frequency of algal blooms [21] as well as increased trace metal concentrations and the presence of invasive species [16]. However, it is not clear whether these effects hold true for smaller still waters such as ponds (<2 ha [22]) as they do lakes.…”
Section: Introductionmentioning
confidence: 99%